Pengaruh Penggunaan Media Pembelajaran Puzzle Terhadap Hasil Belajar Siswa Mata Pelajaran Matematika Materi Bangun Datar Kelas II SD Inpres Belang - Desylia Elisabet Sogen; Yohanes Lawotan; Hermus Hero (Departement of Mathematics Education, 2023)
This study aims to determine the positive effect of using doraemon pouch learning media in improving student learning outcomes in learning mathematics multiplication material for class III students of SDI Belang. This research is a quantitative research. The research method used was pre-experimental using a one-group pretest posttest design. The sample in this study were 20 people. Data collection techniques in this study used tests, observations, and documentation. The results of this research classically show that the average post-test score of students increases after using learning media for Doraemon bags compared to the average pre-test score. The data analysis technique used is statistical analysis of pared samples with the help of the SPSS program. The results of the study show sig = 0.006 ≤ 0.05, it is said that there is a significant difference between the results of the pre-test and post-test which indicates that the alternative hypothesis proposed by the researcher is accepted, namely that there is a positive and significant influence on the use of learning media in Doraemon's pouch in improving learning outcomes students in learning mathematics multiplication material for class III students at SDI Belang.